BİLİMİN METALAŞMASINA BİR YANIT OLARAK YAVAŞ BİLİM. - MORKOÇ, Umut (Community & Physician / Toplum ve Hekim)
The fundamental qualities that distinguish scientific knowledge and claim it as privileged have increasingly come under scrutiny, particularly in the wake of the transformation referred to as the commodifi cation of science, which has been prevalent since the latter half of the 20th century. This shift has raised concerns about distorting the ethos of science, and numerous examples can be cited to justify these apprehensions. The call for “slow science” represents a resistance to this transformation and suggests the possibility of an alternative approach to scientific inquiry.In this study, it will be argued that the call for Slow Science should be considered not only as a demand for a change in scientific practice but also as a resistance against the distortion of the foundational characteristics of science. To achieve this, we will begin by briefly discussing the historical development of the transition from the birth of modern science to the commodification of science in order to comprehend this transformation. We will then address the current and potential consequences of this transformation. Subsequently, we will examine the emergence of the Slow Science movement from within the scientific community as an expression of concern about this transformation and its resulting outcomes. Finally, it will be contended that when the call for Slow Science is considered in conjunction with the developments in contemporary philosophy of science over the past quarter-century, which increasingly emphasize the interaction between science and society, it offers a broader perspective on the possibility of a different kind of science.